The factors that influence intention to subscribe with Takaful among public servant in Perlis - Aidil Syukri, Shaari (2019)
This study deals with factors that influence the intention to subscribe to Takaful among public servants in Perlis. The development of the Takaful industry in Malaysia is an alternative to Shariah-compliant risk management which an option to conventional insurance. Although Takaful and conventional insurance are differences in terms of the contract, the goal of both products is to protect the participants and to help reduce the burden on participants in the event of difficulties or accidents. In this regard, to what extent does the Malaysian community especially Muslims, accept Takaful products and to what extent is the consumer knowledge of the products offered? The number of participants subscribing to Takaful is still low among the community, especially Muslims even though the takaful is Shariah-compliant. Hence, the objective of this study is to identify the factors influencing the intention to subscribe Takaful among public servants in Perlis. This study conducted at Universiti Malaysia Perlis, Perlis where 256 respondents comprised of the technical staff. All hypotheses in this study are tested using Pearson Correlation Analysis, One-way ANOVA and T-test analysis. The results show that financial literacy and social influence have a significant positive relationship with the intention to subscribe to Takaful. It hoped that the results obtained from this study would help to develop the Takaful Industry in Malaysia